Notes on Three Hoards of Coins recently discovered in the South of Scotland - MacDonald, George (Proceedings of the Society of Antiquaries of Scotland, 1914)
A hoard of late Romano-British coins was found at Balgreggan Quarry in Wigtownshire. A total of 125 coins had been concealed in an earthenware jug. Both the coins and the jug were in poor condition. The hoard is thought to have been deposited after AD 354. A fourteenth-century hoard from Kirkcudbrightshire comprised 2222 coins. They included Scottish single long-cross pennies of Alexander III, John Balliol and Robert Bruce along with more than one thousand pennies of Edward I, II and III. They are thought to have been deposited after 1330. A collection of 692 coins of sixteenth century date were found in the recess of a wall during demolition of an old building in Ayr.